What should happen after the death of a probationer? Learning from suicide investigations in prison. (March 2020) - Phillips, Jake
In this comment piece, I explore the relevance of Tomczak's (2019) book Prison Suicide: What Happens Afterwards for those of us working and researching in the field of probation. I argue that many of the findings from Tomczak's research are relevant when thinking about how to enhance accountability and knowledge around the deaths of people under probation supervision.